The covenant with Moses and the kingdom of God: Thomas Hobbes and the theology of the old covenant in early modern England - Martin, Andrew J. (Studies in the history of Christian traditions, 2023)
"Covenant theology was a popular and controversial topic in early modern England. In particular, the biblical old covenant with Moses generated tremendous theological and political debates during the years of the English Civil Wars. And yet, the disciplinary boundaries of historical theology and the history of political thought make it hard to understand why early modern preachers and philosophers wrestled over this topic with such vigour. This interdisciplinary historical theological study explains the development of the covenant theology in the major works of Thomas Hobbes and his contemporaries, including Bishop Robert Sanderson and the puritan and presbyterian circles of the Westminster Assembly"--